The Influence of Price, Promotion, Product Quality, and Consumer Satisfaction on Purchasing Decisions of HAUS! - Assidiki, Zaid; Budiman, Andika Nuraga (SAN Scientific, 2023)
This study aims to examine the effect of price, promotion, product quality and consumer satisfaction on purchasing decisions. The sampling technique used was purposive sampling. The number of samples used was 120 respondents. The sample used in this study is the people of the DKI Jakarta area who have bought the HAUS! beverage product. Data was collected using a survey method with a questionnaire instrument. The data analysis method used is Partial Least Square Structural Equation Modeling analysis. The results showed that (1) price had a positive and significant effect on purchase intention (p-value 0.025) (2) promotion had a positive and significant effect on purchase intention (p-value 0.005) (3) product quality had a positive and significant effect on purchase intention (p-value <0.001) (4) consumer satisfaction has a positive and significant effect on purchase intention (p-value 0.009).